Persistent soil seed banks promote naturalisation and invasiveness in flowering plants - Margherita Gioria; Angelino Carta; Carol C. Baskin; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Mark van Kleunen; Patrick Weigelt; Marten Winter; Petr Pyšek (Ecology Letters, 2021)
With globalisation facilitating the movement of plants and seeds beyond the native range, preventing potentially harmful introductions requires knowledge of what drives the successful establishment and spread of alien plants. Here, we examined global‐scale relationships between naturalisation success (incidence and extent) and invasiveness, soil seed bank properties (type and densities) and key species traits (seed mass, seed dormancy and life form) for 2350 species of angiosperms. Naturalisation and invasiveness were strongly associated with the ability to form persistent (vs. transient) seed banks but relatively weakly with seed bank densities and other traits. Our findings suggest that seed bank persistence is a trait that better captures the ability to become naturalised and invasive compared to seed traits more widely available in trait databases. Knowledge of seed persistence can contribute to our ability to predict global naturalisation and invasiveness and to identify potentially invasive flowering plants before they are introduced.